BREAST NECROSIS IN A CHRONIC USER OF WARFARIN - Cassol, Geraldo Antônio; Morales, Fabrício Farias; Stocco, Mariana Luz; Pinheiro, Mariana Pimenta (Mastology, 2017)
Warfarin-induced skin necrosis is a rare event that generally happens within the first days of warfarin use and is due to the initial, and transitory, prothrombotic state caused by unbalanced pro and anticoagulant factors. We describe the first case of breast necrosis in a 50-year-old woman, who uses warfarin chronically, and had its anticoagulant effect enhanced by the concomitant use of diclofenac.